RANCANG BANGUN SISTEM PENGUKURAN INDEKS KEPUASAN MASYARAKAT (IKM) BERBASIS WEB DI PEMERINTAH KABUPATEN BADUNG - I Komang Suarsana Suarsana; I Gede Juliana Eka Putra; A.A. Istri Ita Paramitha (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
This study focuses on the implementation of the Community Satisfaction Survey (CSS) in Badung Regency, Indonesia, in accordance with the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. In 2022, the Badung Regency Research and Development Agency, in synergy with the Badung Regency Secretariat Organization, conducted an independent survey using Google Forms accessed through employees' mobile phones as survey instruments. However, the processing of survey results was carried out manually using Microsoft Excel. Given these challenges, the author perceives the importance of developing a system designed to measure the Community Satisfaction Index (CSI) online. This research aims to design and develop a web-based CSI Measurement System capable of processing data efficiently. The outcome of this research is expected to be a web-based CSI Measurement System implemented within the Badung Regency Government. With the implementation of this system, it is hoped that the survey process and data processing can be carried out more effectively and efficiently.